Expression of lymphocyte homing receptor antigen in non-Hodgkin's lymphoma. - Picker, L. J. (1988)
In man, lymphocyte binding to high endothelial venules (HEVs) involves specific 85-95 kd cell surface glycoprotein(s) recognized by the monoclonal antibodies Hermes-1 and Hermes-3. These putative "homing receptor" molecule(s) are believed to play an important role in the normal regulation of lymphocyte circulation. To investigate the possibility that homing receptors also play a role in the biology of lymphoid malignancies, the authors studied over 300 cases of non-Hodgkin's lymphoma by immunohistologic staining with Hermes-1 and -3, antibodies that define two distinct epitopes on the gp 85-95 putative homing receptor molecules. Furthermore, they directly compared expression of the Hermes-3 antigen with clinical extent of disease in 57 patients with diffuse large cell lymphoma. They found that staining of the various subtypes of lymphoma was heterogeneous, and in general correlated with patterns of expression seen in benign lymphoid populations. Essentially all normal lymphoid populations examined, except germinal center B cells and most cortical thymocytes, bear a high level of homing receptor antigen. Similarly, nearly all peripheral T-cell lymphomas, diffuse small cell lymphomas of B lineage, and plasma cell tumors were positive for homing receptor antigen (95%, 97%, and 100%, respectively). Small noncleaved cell, follicular, and diffuse large cell lymphomas of B lineage, tumors having morphologic or immunologic features resembling germinal center cells, frequently failed to express Hermes-defined epitopes (81%, 41%, 25% Hermes-3-, respectively). Antigen expression in T-lymphoblastic lymphomas strongly correlated with immunophenotypic subtypes: only 8% of CD4+/CD8+ were Hermes-1+ versus 86% of CD4-/CD8- and 43% of CD4+/CD8-. Hermes-3 expression by cases of diffuse, large cell lymphoma which showed generalized lymph node involvement (a pattern strongly suggestive of HEV-mediated spread; 100% Hermes-3+, mean intensity 3.4) was higher than that of cases with localized or multifocal, contiguous involvement (consistent with lymphatic spread; 69% Hermes-3+, mean intensity 2.2), but these differences did not achieve statistical significance. The results indicate that homing receptor antigen expression, although perhaps necessary for wide-spread blood-borne lymphoma dissemination to lymphoid sites, is not in and of itself sufficient to predict such behavior in this subtype of lymphoid malignancy.